Real time speech enhancement - Soon, Ing Yann. (2008)
Investigation on the speech enhancement algorithms in the transform domain and ways to implement them in real time. The strengths and weaknesses of various transforms such as Discrete Fourier Transform, Discrete Cosine Transform, Karhunen Loeve Transform and Wavelet Transform are also discussed.